PSYCHOLOGICAL SAFETY AS A STRATEGIC ASSET UNDER ADVERSE SHOCKS A COOPERATIVE GAME THEORETIC FRAMEWORK FOR SUPPLY CHAIN RESILIENCE - Taleghani, Mohammad; Sola, Mohammadreza Jabreilzadeh (International Journal of Engineering Technologies and Management Research, 2025)
Purpose – This paper develops the first cooperative game-theoretic model that treats psychological safety as an endogenous strategic asset under Lévy-jump adverse shocks. Design/methodology/approach – A three-player stochastic game (workers, supervisors, suppliers) is calibrated to ILO global injury statistics (2019-2023). A closed-form Psychological-Safety Resilience Index (PSRI) is derived and validated via 5,000 Monte-Carlo paths. Findings – A one-standard-deviation increase in safety climate reduces expected accident cost by 23 % (95 % CI: 21-25 %), an effect equivalent to a 14 % productivity gain. Low-cost behavioral interventions (cost < 1 % payroll) yield an NPV of +8.2 % within 12 months. Originality/value – The PSRI converts intangible trust into a quantifiable dashboard metric, offering managers and policy-makers a scalable lever for supply-chain resilience without additional capital expenditure.